Developing Speaking Skills Through Speaking - Guided Workshops (2016)
This paper aims to share the results of a small-scale research project, focused on developing speaking skills through the implementation of speaking-oriented workshops. The workshops incorporated the use of puppets as an interaction strategy and were based on “healthy lifestyles”, a cross-curricular project developed in the school. This project was carried out with a group of fourth graders in a Colombian public school in Tunja, Boyacá. A field diary, video recordings, interviews and workshops were used to gather information in this action research study. Findings revealed that through the use of these workshops students became more confident and developed their speaking skills while enhancing their cooperative learning abilities